4.5-hour time window for intravenous thrombolysis with recombinant tissue-type plasminogen activator is established firmly - Schellinger, Peter D.; Köhrmann, Martin (Stroke, 2014)
EVALuna2:22310

Adherence to oral anticoagulation in secondary stroke prevention - the first year of direct oral anticoagulants - Sauer, Rolf; Sauer, Eva-Maria; Bobinger, Tobias; Blinzler, Christian; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2015)
Patients with ischemic stroke caused by atrial fibrillation (AF) have a high risk of recurrence without adequate secondary prevention with oral anticoagulation (OAC). We investigated adherence to OAC in the first year after introduction of direct oral anticoagulants.In 284 appropriate patients, the rate of anticoagulation (AC) at discharge, adherence at 90 days and 1 year, changes between substances, and predictors for adherence to AC were analyzed. Functional outcome was assessed using the modified Rankin Scale score.AC was initiated in 70.3% of survivors before discharge. In these patients, only 8.6% and 9.9% discontinued AC after 90 days and 1 year, respectively. In 22.1%, AC was recommended but not started before discharge. Only 53.2% of them received AC at 90 days, increasing to 67.5% at 1 year. A total of 7.6% of patients were deemed unsuitable for AC, none of them subsequently received AC. Overall, 85.4% of patients suitable for AC were treated at 1-year follow-up. No independent predictors for withholding AC were identified. Switching of medication occurred in only a minority of patients within the first year.AC is feasible in more than 90% patients with acute ischemic stroke and AF. When initiated during the acute hospital stay, AC is discontinued in only a minority of patients. However, if AC is recommended but not started during initial hospitalization the rate of AC treatment at 90 days and 1 year is much lower. Therefore, AC should be initiated within the acute hospital stay whenever possible.
EVALuna2:22269

Anticoagulant reversal, blood pressure levels, and anticoagulant resumption in patients with anticoagulation-related intracerebral hemorrhage - Kuramatsu, Joji; Gerner, Stefan; Schellinger, Peter D.; Glahn, Joerg; Endres, Matthias; Sobesky, Jan; Flechsenhar, Julia; Neugebauer, Hermann; Juettler, Eric; Grau, Armin; Palm, Frederick; Roether, Joachim; et al. (Journal of the American Medical Association, 2015)
Although use of oral anticoagulants (OACs) is increasing, there is a substantial lack of data on how to treat OAC-associated intracerebral hemorrhage (ICH).To assess the association of anticoagulation reversal and blood pressure (BP) with hematoma enlargement and the effects of OAC resumption.Retrospective cohort study at 19 German tertiary care centers (2006-2012) including 1176 individuals for analysis of long-term functional outcome, 853 for analysis of hematoma enlargement, and 719 for analysis of OAC resumption.Reversal of anticoagulation during acute phase, systolic BP at 4 hours, and reinitiation of OAC for long-term treatment.Frequency of hematoma enlargement in relation to international normalized ratio (INR) and BP. Incidence analysis of ischemic and hemorrhagic events with or without OAC resumption. Factors associated with favorable (modified Rankin Scale score, 0-3) vs unfavorable functional outcome.Hemorrhage enlargement occurred in 307 of 853 patients (36.0%). Reduced rates of hematoma enlargement were associated with reversal of INR levels <1.3 within 4 hours after admission (43/217 [19.8%]) vs INR of >=1.3 (264/636 [41.5%]; P < .001) and systolic BP <160 mm Hg at 4 hours (167/504 [33.1%]) vs >=160 mm Hg (98/187 [52.4%]; P < .001). The combination of INR reversal <1.3 within 4 hours and systolic BP of <160 mm Hg at 4 hours was associated with lower rates of hematoma enlargement (35/193 [18.1%] vs 220/498 [44.2%] not achieving these values; OR, 0.28; 95% CI, 0.19-0.42; P < .001) and lower rates of in-hospital mortality (26/193 [13.5%] vs 103/498 [20.7%]; OR, 0.60; 95% CI, 0.37-0.95; P = .03). OAC was resumed in 172 of 719 survivors (23.9%). OAC resumption showed fewer ischemic complications (OAC: 9/172 [5.2%] vs no OAC: 82/547 [15.0%]; P < .001) and not significantly different hemorrhagic complications (OAC: 14/172 [8.1%] vs no OAC: 36/547 [6.6%]; P = .48). Propensity-matched survival analysis in patients with atrial fibrillation who restarted OAC showed a decreased HR of 0.258 (95% CI, 0.125-0.534; P < .001) for long-term mortality. Functional long-term outcome was unfavorable in 786 of 1083 patients (72.6%).Among patients with OAC-associated ICH, reversal of INR <1.3 within 4 hours and systolic BP <160 mm Hg at 4 hours were associated with lower rates of hematoma enlargement, and resumption of OAC therapy was associated with lower risk of ischemic events. These findings require replication and assessment in prospective studies.clinicaltrials.gov Identifier: NCT01829581.
EVALuna2:22354

Are Flow Diverting Stents a Treatment Option in Acutely Ruptured Complex A1-A2 Junction Aneurysms? - Roesch, J.; Gölitz, Philipp; Struffert, Tobias; Köhrmann, Martin; Dörfler, Arnd (Clinical Neuroradiology, 2016)
EVALuna2:22379

A simple brain atrophy measure improves the prediction of malignant middle cerebral artery infarction by acute DWI lesion volume - Beck, Christoph; Kruetzelmann, Anna; Forkert, Nils D.; Juettler, Eric; Singer, Oliver C.; Köhrmann, Martin; Kersten, Jan F.; Sobesky, Jan; Gerloff, Christian; Fiehler, Jens; Schellinger, Peter D.; Roether, Joachim; et al. (Journal of Neurology, 2014)
In patients with malignant middle cerebral artery infarction (MMI) decompressive surgery within 48 h improves functional outcome. In this respect, early identification of patients at risk of developing MMI is crucial. While the acute diffusion weighted imaging (DWI) lesion volume was found to predict MMI with high predictive values, the potential impact of preexisting brain atrophy on the course of space-occupying middle cerebral artery (MCA) infarction and the development of MMI remains unclear. We tested the hypothesis that the combination of the acute DWI lesion volume with simple measures of brain atrophy improves the early prediction of MMI. Data from a prospective, multicenter, observational study, which included patients with acute middle cerebral artery main stem occlusion studied by MRI within 6 h of symptom onset, was analyzed retrospectively. The development of MMI was defined according to the European randomized controlled trials of decompressive surgery. Acute DWI lesion volume, as well as brain and cerebrospinal fluid volume (CSF) were delineated. The intercaudate distance (ICD) was assessed as a linear brain atrophy marker by measuring the hemi-ICD of the intact hemisphere to account for local brain swelling. Binary logistic regression analysis was used to identify significant predictors of MMI. Cut-off values were determined by Classification and Regression Trees analysis. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the resulting models were calculated. Twenty-one (18 %) of 116 patients developed a MMI. Malignant middle cerebral artery infarctions patients had higher National Institutes of Health Stroke Scale scores on admission and presented more often with combined occlusion of the internal carotid artery and MCA. There were no differences in brain and CSF volume between the two groups. Diffusion weighted imaging lesion volume was larger (p < 0.001), while hemi-ICD was smaller (p = 0.029) in MMI patients. Inclusion of hemi-ICD improved the prediction of MMI. Best cut-off values to predict the development of MMI were DWI lesion volume > 87 ml and hemi-ICD <= 9.4 mm. The addition of hemi-ICD to the decision tree strongly increased PPV (0.93 vs. 0.70) resulting in a reduction of false positive findings from 7/23 (30 %) to 1/15 (7 %), while there were only slight changes in specificity, sensitivity and NPV. The absolute number of correct classifications increased by 4 (3.4 %). The integration of hemi-ICD as a linear marker of brain atrophy, that can easily be assessed in an emergency setting, may improve the prediction of MMI by lesion volume based predictive models.
EVALuna2:22309

Cerebrovascular complications of immunologically mediated heparin-induced thrombocytopenia - Macha, K.; Kloska, Stephan; Dörfler, Arnd; Raaz-Schrauder, D.; Schwab, Sibylle; Köhrmann, Martin; Seifert, Frank (Fortschritte der Neurologie - Psychiatrie, 2014)
Immunologically mediated heparin-induced thrombocytopenia (HIT) is a thrombotic disease caused by antibodies occurring after heparin exposure. Thrombocytopenia occurs within a few days after heparin exposure, about half of HIT-patients develop venous or arterial thrombotic complications. Neurological complications of HIT are mainly ischaemic stroke and sinus vein thrombosis. To ensure the primary clinical diagnosis functional and immunological assays for antibody detection are available. The probability for the occurrence of HIT depends on the nature of heparin employed (LMWH vs. UFH) and individual patient characteristics such as gender and primary disease (medical vs. surgical patients). In the case of suspected HIT heparin administration should be discontinued immediately and replaced by an alternative anticoagulation to prevent the expansion or development of further thrombotic complications. Herein we report a case of a patient suffering from HIT-associated embolic cerebral ischaemic stroke.
EVALuna2:22326

Clinical and radiological outcome after mechanical thrombectomy in acute ischemic stroke: What matters? - Kaschka, Iris; Kloska, Stephan; Struffert, Tobias; Engelhorn, Tobias; Gölitz, Philipp; Kurka, Natalia; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd (Neuroradiology Journal, 2016)
Recent studies have shown the efficacy of mechanical thrombectomy in acute ischemic stroke. We sought to identify prognostic parameters for clinical and radiological outcome after mechanical thrombectomy.In 34 patients (age 72 ± 13 years, 64.7% women) with acute occlusion of the distal ICA and/or M1 segment who were treated with mechanical thrombectomy, the Spearman correlation was performed to assess potential prognostic outcome parameters (age, NIHSS, ASPECT, thrombus length (TL), clot burden score (CBS), relative filling time delay (rFTD), time to recanalization (TTR) and TICI score). The modified Rankin scale (mRS) and the Alberta Stroke Program Early CT (ASPECT) score were used for clinical and radiological outcome, respectively. Receiver operating characteristic (ROC) analysis was performed to assess parameters predicting favorable clinical (?mRS <= 2) and radiological outcome (?ASPECT <= 2).Variables associated with favorable clinical outcome included NIHSS, TL, TTR and TICI score (p <= 0.01) with NIHSS <= 15 (p = 0.001, area under the curve (AUC) 0.87), TL <= 2 cm (p = 0.017, AUC 0.75), TTR <= 231 min (p = 0.001 AUC 0.88) and TICI >= 2b (p = 0.050, AUC 0.70). Shorter TTR and higher TICI scores were associated with favorable radiological outcome (p < 0.001) with TTR <= 224 min (p = 0.023, AUC 0.77) and TICI >= 2b (p = 0.000, AUC 0.86).Fast and complete recanalization is essential to achieve a favorable radiological and functional outcome after mechanical thrombectomy in acute ischemic stroke. Age, CBS and collateral supply play a subordinate role.
EVALuna2:22544

Clinical/perfusion CT CBV mismatch as prognostic factor in intraarterial thrombectomy in acute anterior circulation stroke - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd; Kloska, Stephan (Clinical Neurology and Neurosurgery, 2014)
Contradictory results were reported for the outcome after endovascular recanalization (ERT) in acute anterior circulation ischemic stroke. We assessed whether a clinical/perfusion CT cerebral blood volume (CBV) mismatch concept (CPM) can identify patients who will benefit from reperfusion therapy.Imaging and clinical data of 58 consecutive ERT cases with acute anterior circulation stroke (ICA, M1, proximal M2) undergoing intraarterial thrombectomy within 4.5h after symptom onset were analyzed retrospectively. CPM was defined as NIHSS>=8 and PCT CBV ASPECTS>=7. Minor CBV lesion was defined as PCT CBV ASPECTS>=7.All baseline characteristics other than blood glucose did not differ between the paired groups. Revascularization was achieved in 87.9% of all patients without significant difference between the paired groups. Favorable clinical outcome after 3 months (mRS<=2) resulted in 29.3% of all patients, in contrast to 47.4% of the CPM positive and 52.2% of the minor CBV lesion groups.CPM can identify patients who will benefit from reperfusion therapy in acute anterior circulation ischemic stroke.
EVALuna2:14386

Clinical/scientific notes - Möller, Sebastian; Hilz, Max-Josef; Blinzler, C.; Köhn, Julia; Dörfler, Arnd; Schwab, Stefan; Köhrmann, Martin (Neurology, 2012)
CRIS-Team Scopus Importer:2022-08-05

Clot Burden and Collaterals in Anterior Circulation Stroke: Differences Between Single-Phase CTA and Multi-phase 4D-CTA - Kaschka, Iris; Kloska, Stephan; Struffert, Tobias; Engelhorn, Tobias; Gölitz, Philipp; Kurka, Natalia; Köhrmann, Martin; Schwab, Siegfried; Dörfler, Arnd (Clinical Neuroradiology, 2014)
It has been reported that the extent of intravascular thrombi and the quality of collateral filling in computed tomography (CT) angiography are predictive for the clinical outcome in patients with acute stroke. We hypothesized that multi-phase four-dimensional CTA (4D-CTA) allows better assessment of clot burden and collateral flow compared with arterial single-phase CTA (CTA).In 49 patients (33 female; age: 77 ± 12 years) with acute anterior circulation stroke, CTA and 4D-CTA reconstructed from dynamic perfusion CT data were analyzed for absolute thrombus length (TL), clot burden score (CBS), and collateral score (CS). The length of the filling defect was also defined on thin-slice nonenhanced CT as corresponding hyperdense middle cerebral artery sign (HMCAS) when present.There was good correlation (r = 0.62, p < 0.01) between the length of HMCAS (1.29 ± 0.62 cm) and TL in 4D-CTA (1.22 ± 0.51 cm). 4D-CTA and CTA significantly varied (p < 0.01) in TL (1.42 ± 0.73 cm (CTA) versus 1.11 ± 0.62 cm (4D-CTA)), CBS (median: 5, interquartile range: 4-7 (CTA) versus median: 6, interquartile range: 5-8 (4D-CTA); p < 0.001), and CS (median: 2, interquartile range: 1-2 (CTA) versus median: 3, interquartile range: 2-3 (4D-CTA); p < 0.001). Accordingly, CTA significantly overrated clot burden and underestimated collateral flow.4D-CTA more closely defines clot burden and collateral supply in anterior circulation stroke than CTA, implicating an additional diagnostic benefit.
EVALuna2:22276

Combined lysis of thrombus with ultrasound and systemic tissue plasminogen activator for emergent revascularization in acute ischemic stroke (CLOTBUST-ER): design and methodology of a multinational phase 3 trial - Schellinger, Peter D.; Alexandrov, Andrei V.; Barreto, Andrew D.; Demchuk, Andrew M.; Tsivgoulis, Georgios; Köhrmann, Martin; Alleman, John; Howard, Virginia; Howard, George; Alexandrov, Anne W.; Brandt, Gordon; Molina, Carlos A. (International Journal of Stroke, 2015)
We designed a Phase 3 clinical trial to determine the safety and efficacy of adding transcranial ultrasound using an operator-independent headframe to recombinant tissue-plasminogen-activator for the treatment of acute ischemic stroke.Combined lysis of thrombus with ultrasound and systemic tissue-plasminogen-activator for emergent revascularization in acute ischemic stroke is a randomized, double-blind, placebo-controlled clinical trial that will enroll subjects with the following main inclusion criteria: less than 4·5 hours from symptom onset (three-hours in US and Canada), age 18-80 years, baseline National Institutes of Health Stroke Scale score >= 10, and premorbid modified-Rankin-score of 0-1, eligibility for full dose recombinant tissue-plasminogen-activator. Subjects will receive two-hours of 2-MHz pulsed wave transcranial ultrasound (target group) or sham ultrasound (control group). The projected sample size is approximately 824 subjects.The primary endpoint, based on intention-to-treat criteria of patients enrolled within three-hours of symptom onset is the comparison between target and control groups of modified-Rankin-score scores at day 90 poststroke assessed using the proportional odds method. The study will have two planned interim analyses after approximately one-third and two-thirds of subjects have reached the 90-day modified-Rankin-score evaluation. Safety outcomes are symptomatic intracranial hemorrhage within 24 h and an overall analysis of adverse events.Since intravenous recombinant tissue-plasminogen-activator remains the only medical therapy to reverse ischemic stroke applicable in the emergency department, our trial will determine if the additional use of transcranial ultrasound improves functional outcomes in patients with severe acute ischemic stroke (NCT#01098981).
EVALuna2:22372

Combining magnetic resonance imaging within six-hours of symptom onset with clinical follow-up at 24 h improves prediction of 'malignant' middle cerebral artery infarction - Kruetzelmann, Anna; Hartmann, Frank; Beck, Christoph; Juettler, Eric; Singer, Oliver C.; Köhrmann, Martin; Kersten, Jan F.; Sobesky, Jan; Gerloff, Christian; Villringer, Arno; Fiehler, Jens; Neumann-Haefelin, Tobias; et al. (International Journal of Stroke, 2014)
A large diffusion-weighted imaging lesion <=six-hours of symptom onset was found to predict the development of 'malignant' middle cerebral artery infarction with high specificity, positive predictive value, and negative predictive value, but sensitivity was low.We tested the hypothesis that sensitivity can be improved by adding information from clinical follow-up examination after 24 h.We analyzed data from a prospective, multicenter, observational cohort study of patients with acute ischemic stroke and middle cerebral artery occlusion studied by stroke magnetic resonance imaging <=six-hours of symptom onset. We used the National Institutes of Health Stroke Scale to assess severity of symptoms after 24 h. We used the Classification and Regression Trees analysis to define the optimal thresholds of diffusion-weighted imaging lesion volume and the National Institutes of Health Stroke Scale after 24 h in patients developing 'malignant' middle cerebral artery infarction. We calculated sensitivity, specificity, positive predictive value, and negative predictive value for two simple predictive models based on acute diffusion-weighted imaging lesion volume alone and acute diffusion-weighted imaging lesion volume together with the National Institutes of Health Stroke Scale after 24 h.Of 135 patients, 27 (20%) developed a 'malignant' middle cerebral artery infarction. The Classification and Regression Trees analysis identified acute diffusion-weighted imaging lesion >=78 ml and the National Institutes of Health Stroke Scale score after 24 h >=22 as optimal cut-offs. Inclusion of the National Institutes of Health Stroke Scale score after 24 h in a simple two-step decision tree increased sensitivity from 0·59 to 0·79, while specificity, positive predictive value, and negative predictive value remained largely unchanged.Clinical follow-up examination after 24 h helps identify patients at risk of 'malignant' middle cerebral artery infarction that are missed by predictive algorithms based on early diffusion-weighted imaging lesion volume alone.
EVALuna2:22296

Comparative efficacy of different acute reperfusion therapies for acute ischemic stroke: a comprehensive benefit-risk analysis of clinical trials - Tsivgoulis, Georgios; Alleman, John; Katsanos, Aristeidis H.; Barreto, Andrew D.; Köhrmann, Martin; Schellinger, Peter D.; Molina, Carlos A.; Alexandrov, Andrei V. (Brain and Behavior, 2014)
Numerous acute reperfusion therapies (RPT) are currently investigated as potential new therapeutic targets in acute ischemic stroke (AIS). We conducted a comprehensive benefit-risk analysis of available clinical studies assessing different acute RPT, and investigated the utility of each intervention in comparison to standard intravenous thrombolysis (IVT) and in relation to the onset-to-treatment time (OTT).A comprehensive literature search was conducted to identify all available published, peer-reviewed clinical studies that evaluated the efficacy of different RPT in AIS. Benefit-to-risk ratio (BRR), adjusted for baseline stroke severity, was estimated as the percentage of patients achieving favorable functional outcome (BRR1, mRS score: 0-1) or functional independence (BRR2, mRS score: 0-2) at 3 months divided by the percentage of patients who died during the same period.A total of 18 randomized (n = 13) and nonrandomized (n = 5) clinical studies fulfilled our inclusion criteria. IV therapy with tenecteplase (TNK) was found to have the highest BRRs (BRR1 = 5.76 and BRR2 = 6.82 for low-dose TNK; BRR1 = 5.80 and BRR2 = 6.87 for high-dose TNK), followed by sonothrombolysis (BRR1 = 2.75 and BRR2 = 3.38), while endovascular thrombectomy with MERCI retriever was found to have the lowest BRRs (BRR1 range, 0.31-0.65; BRR2 range, 0.52-1.18). A second degree negative polynomial correlation was detected between favorable functional outcome and OTT (R (2) value: 0.6419; P < 0.00001) indicating the time dependency of clinical efficacy of all reperfusion therapies.Intravenous thrombolysis (IVT) with TNK and sonothrombolysis have the higher BRR among investigational reperfusion therapies. The combination of sonothrombolysis with IV administration of TNK appears a potentially promising therapeutic option deserving further investigation.
EVALuna2:22321

Consensus statements and recommendations from the ESO-Karolinska Stroke Update Conference, Stockholm 11-13 November 2018 - Ahmed, Niaz; Audebert, Heinrich; Turc, Guillaume; Cordonnier, Charlotte; Christensen, Hanne; Sacco, Simona; Sandset, Else Charlotte; Ntaios, George; Charidimou, Andreas; Toni, Danilo; Pristipino, Christian; Köhrmann, Martin; et al. (European Stroke Journal, 2019)
The purpose of the European Stroke Organisation-Karolinska Stroke Update Conference is to provide updates on recent stroke therapy research and to give an opportunity for the participants to discuss how these results may be implemented into clinical routine. The meeting started 22 years ago as Karolinska Stroke Update, but since 2014 it is a joint conference with European Stroke Organisation. Importantly, it provides a platform for discussion on the European Stroke Organisation guidelines process and on recommendations to the European Stroke Organisation guidelines committee on specific topics. By this, it adds a direct influence from stroke professionals otherwise not involved in committees and work groups on the guideline procedure. The discussions at the conference may also inspire new guidelines when motivated. The topics raised at the meeting are selected by the scientific programme committee mainly based on recent important scientific publications. This year's European Stroke Organisation-Karolinska Stroke Update Meeting was held in Stockholm on 11-13 November 2018. There were 11 scientific sessions discussed in the meeting including two short sessions. Each session except the short sessions produced a consensus statement (Full version with background, issues, conclusions and references are published as web-material and at and ) and recommendations which were prepared by a writing committee consisting of session chair(s), scientific secretary and speakers. These statements were presented to the 250 participants of the meeting. In the open meeting, general participants commented on the consensus statement and recommendations and the final document were adjusted based on the discussion from the general participants Recommendations (grade of evidence) were graded according to the 1998 Karolinska Stroke Update meeting with regard to the strength of evidence. Grade A Evidence: Strong support from randomised controlled trials and statistical reviews (at least one randomised controlled trial plus one statistical review). Grade B Evidence: Support from randomised controlled trials and statistical reviews (one randomised controlled trial or one statistical review). Grade C Evidence: No reasonable support from randomised controlled trials, recommendations based on small randomised and/or non-randomised controlled trials evidence.
CRIS-Team WoS Importer:2019-09-24

Dabigatran Plasma Levels in Acute Cerebrovascular Events - Volbers, Bastian; Köhrmann, Martin; Kallmünzer, Bernd; Kurka, Natalia; Breuer, Lorenz; Ringwald, Juergen; Schwab, Stefan (Journal of Stroke and Cerebrovascular Diseases, 2016)
Oral anticoagulation with dabigatran was shown to be effective for stroke prevention in patients with nonvalvular atrial fibrillation without the need for laboratory monitoring. However, a recent publication based on data of the Randomized Evaluation of Long-Term Anticoagulation Therapy study reported that ischemic stroke and bleeding outcomes are correlated with dabigatran plasma concentration (DPC). DPC was determined at a prespecified time point and correlated with cardiovascular events at any time during follow-up. Because of the known variability of DPC, among others depending on renal function, this approach might compromise data evaluation. We report on dabigatran plasma levels in acute cerebrovascular events.Consecutive patients with acute ischemic stroke (AIS) or intracerebral hemorrhage (ICH) while taking dabigatran were retrospectively identified if admission DPC was available. DPC was determined using the diluted thrombin time (Hemoclot (HYPHEN BioMed, Neuville sur Oise, France)). Creatinine clearance (CrCl) was determined by measuring creatinine in plasma and 24-hour urine.Fifteen AIS and 4 ICH patients were included. Median DPC on admission was significantly higher in ICH patients than in AIS patients (135 ng/mL [interquartile range IQR 79-218] and 69.1 ng/mL [IQR 20.6-85.0], respectively; P = .035). Increased CrCl (values above published normal range) was correlated with lower median DPC (60 ng/mL [IQR 10-69] versus 100 ng/mL [IQR 79-157] in patients with normal CrCl, P = .01).Higher DPC was found in ICH patients than in AIS patients in temporal proximity to the event. Both decreased and increased renal functions seem to have an important influence on DPC.
EVALuna2:15996

Diagnostic value of prehospital ECG in acute stroke patients - Bobinger, Tobias; Kallmnzer, Bernd; Kopp, Markus; Kurka, Natalia; Heider, Stefan; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Neurology, 2017)
To investigate the diagnostic yield of prehospital ECG monitoring provided by emergency medical services in the case of suspected stroke.Consecutive patients with acute stroke admitted to our tertiary stroke center via emergency medical services and with available prehospital ECG were prospectively included during a 12-month study period. We assessed prehospital ECG recordings and compared the results to regular 12-lead ECG on admission and after continuous ECG monitoring at the stroke unit.Overall, 259 patients with prehospital ECG recording were included in the study (90.3% ischemic stroke, 9.7% intracerebral hemorrhage). Atrial fibrillation (AF) was detected in 25.1% of patients, second-degree or greater atrioventricular block in 5.4%, significant ST-segment elevation in 5.0%, and ventricular ectopy in 9.7%. In 18 patients, a diagnosis of new-onset AF with direct clinical consequences for the evaluation and secondary prevention of stroke was established by the prehospital recordings. In 2 patients, the AF episodes were limited to the prehospital period and were not detected by ECG on admission or during subsequent monitoring at the stroke unit. Of 126 patients (48.6%) with relevant abnormalities in the prehospital ECG, 16.7% received medical antiarrhythmic therapy during transport to the hospital, and 6.4% were transferred to a cardiology unit within the first 24 hours in the hospital.In a selected cohort of patients with stroke, the in-field recordings of the ECG detected a relevant rate of cardiac arrhythmia. The results can add to the in-hospital evaluation and should be considered in prehospital care of acute stroke.
EVALuna2:22506

Doppler pulsatility index in spontaneous intracerebral hemorrhage - Kiphuth, Ines C.; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Köhrmann, Martin (European neurology, 2013)
Background and Purpose: Elevated intracranial pressure (ICP) as a result of intracerebral hemorrhage (ICH) and perihematomal edema often leads to tissue shift, which can be identified in cross-sectional imaging and presents a known predictor of functional outcome. Pulsatility indices (PIs) of the intracranial arteries as measured by transcranial Doppler sonography (TCD) may serve as surrogate parameters for ICP. This study aims to investigate whether PI correlates with ICP and midline shift and serves as a reliable predictor of functional outcome in patients with ICH. Methods: Within a 1-year period between April 2009 and April 2010, 136 patients with acute spontaneous, supratentorial ICH were admitted to our tertiary care hospital. One-hundred and twenty-four patients fulfilled the inclusion criteria and were eligible for analysis. TCD and transcranial duplex sonography were performed on admission and at least once more during hospital stay. Functional outcome was assessed 6 months after discharge. Correlation analyses, logistic regression analyses and receiver operating characteristic curves were calculated. Results: One-hundred and twenty-four patients were included in the analysis. Six-month mortality amounted to 39.5%. The ICH score and PIs of the middle cerebral artery were independent predictors of outcome 6 months after discharge. Conclusions: Early PI monitoring by TCD correlated with ICP and may be used to predict the outcome after 6 months. Copyright © 2013 S. Karger AG, Basel.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Functional outcome; Intracerebral hemorrhage; Midline shift; Pulsatility index; Transcranial duplex sonography

Early Initiation of Anticoagulation with Direct Oral Anticoagulants in Patients after Transient Ischemic Attack or Ischemic Stroke - Macha, Kosmas; Volbers, Bastian; Bobinger, Tobias; Kurka, Natalia; Breuer, Lorenz; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2016)
Direct oral anticoagulants (DOACs) are increasingly used for secondary prevention of cardioembolic stroke. While DOACs are associated with a long-term reduced risk of intracranial hemorrhage compared to vitamin K antagonists, pivotal trials avoided the very early period after stroke and few data exist on early initiation of DOAC therapy post stroke.We retrospectively analyzed data from our prospective database of all consecutive transient ischemic attack (TIA) or ischemic stroke patients with atrial fibrillation treated with DOACs during hospital stay. As per our institutional treatment algorithm for patients with cardioembolic ischemia DOACs are started immediately in TIA and minor stroke (group 1), within days 3-5 in patients with infarcts affecting one third or less of the middle cerebral artery, the anterior cerebral artery, or the posterior cerebral artery territories (group 2) as well as in infratentorial stroke (group 3) and after 1-2 weeks in patients with large infarcts (> 1/3 MCA territory, group 4). We investigated baseline characteristics, time to initiation of DOAC therapy after symptom onset, and hemorrhagic complications.In 243 included patients, administration of DOAC was initiated 40.5 hours (interquartile range [IQR] 23.0-65.5) after stroke onset in group 1 (n = 41) and after 76.7 hours (IQR 48.0-134.0), 108.4 hours (IQR 67.3-176.4), and 161.8 hours (IQR 153.9-593.8) in groups 2-4 (n = 170, 28, and 4), respectively. Two cases of asymptomatic intracranial hemorrhage (.8%) and 1 case of symptomatic intracranial hemorrhage (.4%) were observed, both in group 2.No severe safety issues were observed in early initiation of DOACs for secondary prevention after acute stroke in our in-patient cohort.
EVALuna2:22461

Endovascular equipoise shift in a phase III randomized clinical trial of sonothrombolysis for acute ischemic stroke - Alexandrov, Andrei V.; Tsivgoulis, Georgios; Köhrmann, Martin; Katsanos, Aristeidis H.; Soinne, Lauri; Barreto, Andrew D.; Rothlisberger, Travis; Sharma, Vijay K.; Mikulik, Robert; Muir, Keith W.; Levi, Christopher R.; Molina, Carlos A.; et al. (Therapeutic Advances in Neurological Disorders, 2019)
Background: Results of our recently published phase III randomized clinical trial of ultrasound-enhanced thrombolysis (sonothrombolysis) using an operator-independent, high frequency ultrasound device revealed heterogeneity of patient recruitment among centers. Methods: We performed a post hoc analysis after excluding subjects that were recruited at centers reporting a decline in the balance of randomization between sonothrombolysis and concurrent endovascular trials. Results: From a total of 676 participants randomized in the CLOTBUST-ER trial we identified 52 patients from 7 centers with perceived equipoise shift in favor of endovascular treatment. Post hoc sensitivity analysis in the intention-to-treat population adjusted for age, National Institutes of Health Scale score at baseline, time from stroke onset to tPA bolus and baseline serum glucose showed a significant (p < 0.01) interaction of perceived endovascular equipoise shift on the association between sonothrombolysis and 3 month functional outcome [adjusted common odds ratio (cOR) in centers with perceived endovascular equipoise shift: 0.22, 95% CI 0.06–0.75; p = 0.02; adjusted cOR for centers without endovascular equipoise shift: 1.20, 95% CI 0.89–1.62; p = 0.24)]. After excluding centers with perceived endovascular equipoise shift, patients randomized to sonothrombolysis had higher odds of 3 month functional independence (mRS scores 0–2) compared with patients treated with tPA only (adjusted OR: 1.53; 95% CI 1.01–2.31; p = 0.04). Conclusion: Our experience in CLOTBUST-ER indicates that increasing implementation of endovascular therapies across major academic stroke centers raises significant challenges for clinical trials aiming to test noninterventional or adjuvant reperfusion strategies.
CRIS-Team Scopus Importer:2019-07-23
Keywords: endovascular; equipoise shift; intracranial hemorrhage; mechanical thrombectomy; outcome; recanalization; sonothrombolysis; stroke; ultrasound-enhanced thrombolysis

Erectile dysfunction (ED) after ischemic stroke: association between prevalence and site of lesion - Koehn, Julia; Crodel, Carl; Deutsch, Martina; Kolominsky-Rabas, Peter; Hoesl, Katharina M.; Köhrmann, Martin; Schwab, Stefan; Hilz, Max-Josef (Clinical Autonomic Research, 2015)
Stroke may cause or worsen erectile dysfunction (ED). Post-stroke ED prevalence and association with stroke location are not well established. Therefore, we assessed post-stroke ED prevalence in relation to ischemic lesion locations and stroke severity.In 57 men (62.6 ± 10.5 years) who had ischemic stroke within 24 months prior to evaluation, we used the five-item International Index of Erectile Function questionnaire (IIEF5) to evaluate ED prevalence after stroke and retrospectively 3 months prior to stroke. IIEF5 scores range from 5 to 25; scores below 22 indicate ED. We estimated stroke severity upon hospital admission, using the National Institute of Health Stroke Scale (NIHSS), and determined stroke location from cranial computed tomography or magnetic resonance imaging. We compared pre- and post-stroke results with those of 22 control persons (61.7 ± 11.2 years), calculated correlations between IIEF5 scores and NIHSS scores, and compared ED prevalence with stroke locations (significance: p < 0.05).ED was reported by 45/57 patients after stroke, 26/57 patients before stroke, and 6/22 control persons. Patients' IIEF5 values were significantly lower [median 16 interquartile range (IQR) 3.5-20.5] after than before stroke (median 23, IQR 19.0-24.0) and lower than in controls (median 24, IQR 19.8-25.0). Pre- and post-stroke IIEF5 scores did not correlate with the patients' NIHSS scores at stroke onset (p > 0.05). ED was associated with middle cerebral artery infarction in 27/34, posterior cerebral artery infarction in 4/5, anterior cerebral artery infarction in 1/1, basal ganglia infarction in 3/3, brain stem infarction in 8/10, cerebellar infarction in 2/5, and lesions in more than one region in 1/1 patients.Disruption of the central network assuring erection might contribute to increased ED severity and prevalence after stroke. Anti-erectile effects of functional and psychological impairment or medication added after stroke may also contribute to ED but must be evaluated in larger patients groups.
EVALuna2:22368

Erratum to 'Clinical/perfusion CT CBV mismatch as prognostic factor in intraarterial thrombectomy in acute anterior circulation stroke' (Clinical Neurology and Neurosurgery (2014) 121, (39-45)) - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd; Kloska, Stephan (Clinical Neurology and Neurosurgery, 2014)
CRIS-Team Scopus Importer:2022-08-05

Feasibility of certified quality management in a comprehensive stroke care network using telemedicine: STENO project - Handschu, Rene; Scibor, Mateusz; Wacker, Angela; Stark, David Rianto; Köhrmann, Martin; Erbguth, Frank; Oschmann, Patrick; Schwab, Stefan; Marquardt, Lars (International Journal of Stroke, 2014)
Stroke care networks with and without telemedicine have been established in several countries over the last decade to provide specialized stroke expertise to patients in rural areas. Acute consultation is a first step in the management of stroke, but not the only one. Methods of standardization of care and treatment are much needed. So far, quality management systems have only been used for single stroke units. To the best of our knowledge, we are the first stroke network worldwide to aim for certification of a network-wide quality management system.The Stroke Network Using Telemedicine in Northern Bavaria (STENO), currently with 20 associated medical institutions, is one of the world's largest stroke networks, caring for over 5000 stroke patients each year. In 2010, we initiated the implementation of a network-wide 'total' quality management system according to ISO standard 9001:2008 in cooperation with the German Stroke Society and a third-party certification organization (LGA InterCert).Certification according to ISO 9001:2008 was awarded in March 2011 and maintained over a complete certification cycle of 3 years without major deviation from the norm in three external third-party audits. Thrombolysis rate significantly increased from 8·2% (2009) to 12·8% (2012).Certified quality management within a large stroke network using telemedicine is possible and might improve stroke care procedures and thrombolysis rates. Outcome studies comparing conventional stroke care and telestroke care are inevitable.
EVALuna2:22263

Functional Outcome of Intravenous Thrombolysis in Patients With Lacunar Infarcts in the WAKE-UP Trial - Barow, Ewgenia; Boutitie, Florent; Cheng, Bastian; Cho, Tae-Hee; Ebinger, Martin; Endres, Matthias; Fiebach, Jochen B.; Fiehler, Jens; Ford, Ian; Galinovic, Ivana; Nickel, Alina; Puig, Josep; et al. (JAMA Neurology, 2019)
IMPORTANCE The rationale for intravenous thrombolysis in patients with lacunar infarcts is debated, since it is hypothesized that the microvascular occlusion underlying lacunar infarcts might not be susceptible to pharmacological reperfusion treatment.
CRIS-Team WoS Importer:2019-07-26

Hematoma Characteristics and Functional Outcome Do Not Differ in NOAC- Versus VKA-Associated Intracerebral Hemorrhage - Gerner, Stefan; Lücking, Hannes; Köhrmann, Martin; Huttner, Hagen (2016)
EVALuna2:22585

Hyponatremia is an independent predictor of in-hospital mortality in spontaneous intracerebral hemorrhage - Kuramatsu, Joji; Bobinger, Tobias; Volbers, Bastian; Staykov, Dimitre; Lücking, Hannes; Kloska, Stephan; Köhrmann, Martin; Huttner, Hagen (Stroke, 2014)
Hyponatremia is the most frequent electrolyte disturbance in critical care. Across various disciplines, hyponatremia is associated with increased mortality and longer hospital stay, yet in intracerebral hemorrhage (ICH) no data are available. This the first study that investigated the prevalence and clinical associations of hyponatremia in patients with ICH.This observational study included all consecutive spontaneous ICH patients (n=464) admitted during a 5-year period to the Department of Neurology. Patient characteristics, in-hospital measures, mortality, and functional outcome (90 days and 1 year) were analyzed to determine the effects of hyponatremia (Na<135 mEq/L). Multivariable regression analyses were calculated for factors associated with hyponatremia and predictors of in-hospital mortality.The prevalence of hyponatremia on hospital admission was 15.6% (n=66). Normonatremia was achieved and maintained in almost all hyponatremia patients<48 hours. In-hospital mortality was roughly doubled in hyponatremia compared with nonhyponatremia patients (40.9%; n=27 versus 21.1%; n=75), translating into a 2.5-fold increased odds ratio (P<0.001). Multivariable analyses identified hyponatremia as an independent predictor of in-hospital mortality (odds ratio, 2.2; 95% confidence interval, 1.05-4.62; P=0.037). Within 90 days after ICH, hyponatremia patients surviving hospital stay were also at greater risk of death (odds ratio, 4.8; 95% confidence interval, 2.1-10.6; P<0.001); thereafter, mortality rates were similar.Hyponatremia was identified as an independent predictor of in-hospital mortality with a fairly high prevalence in spontaneous ICH patients. The presence of hyponatremia at hospital admission is related to an increased short-term mortality in patients surviving acute care, possibly reflecting a preexisting condition that is linked to worse outcome due to greater comorbidity. Correction of hyponatremia does not seem to compensate its influence on mortality, which strongly warrants future research.
EVALuna2:22304

Impact of heart rate dynamics on mortality in the early phase after ischemic stroke: a prospective observational trial - Kallmünzer, Bernd; Bobinger, Tobias; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Journal of Stroke and Cerebrovascular Diseases, 2015)
Growing evidence suggests that the heart rate (HR) at rest is an independent predictor of cardiovascular mortality. In ischemic stroke, continuous monitoring of HR is the standard of care, but systematic data on its dynamics and prognostic value during the acute phase are limited.In this prospective observational study, HR was measured by continuous electrocardiographic monitoring on admission and during the first 72 hours of care among patients who were awake with ischemic stroke and survived until discharge. Functional outcome was assessed after 90 days.Data from 702 consecutive patients were analyzed (median age, 73 years, 54% men). The time course of HR was initially characterized by a rapid decline during the first 12 hours after admission. Among patients who survived until day 90, this was followed by a continuous downward trend in HR, whereas death after discharge was associated with a secondary increase and a reversal point 12 hours after admission. After adjustment for established risk factors, this secondary increase during the acute period was an independent predictor of death (hazard ratio, 3.73; 95% confidence interval, 1.47-9.43; P = .005).A secondary rise of HR during care for acute ischemic stroke is an early sign of fatality and may represent a surrogate for an unfavorable sympathetic disinhibition. Further research is warranted to clarify the role of targeted HR reduction after ischemic stroke (http://clinicaltrials.gov/, unique identifier NCT01858779).
EVALuna2:12023

Impact of Lesion Load Thresholds on Alberta Stroke Program Early Computed Tomographic Score in Diffusion-Weighted Imaging - Schroeder, Julian; Cheng, Bastian; Malherbe, Caroline; Ebinger, Martin; Köhrmann, Martin; Wu, Ona; Kang, Dong-Wha; Liebeskind, David S.; Tourdias, Thomas; Singer, Oliver C.; Campbell, Bruce; Luby, Marie; et al. (Frontiers in Neurology, 2018)
Background and aims: Assessment of ischemic lesions on computed tomography or MRI diffusion-weighted imaging (DWI) using the Alberta Stroke Program Early Computed Tomography Score (ASPECTS) is widely used to guide acute stroke treatment. However, it has never been defined how many voxels need to be affected to label a DWI-ASPECTS region ischemic. We aimed to assess the effect of various lesion load thresholds on DWI-ASPECTS and compare this automated analysis with visual rating. Materials and methods: We analyzed overlap of individual DWI lesions of 315 patients from the previously published predictive value of fluid-attenuated inversion recovery study with a probabilistic ASPECTS template derived from 221 CT images. We applied multiple lesion load thresholds per DWI-ASPECTS region (>0, >1, >10, and >20% in each DWI-ASPECTS region) to compute DWI-ASPECTS for each patient and compared the results to visual reading by an experienced stroke neurologist. Results: By visual rating, median ASPECTS was 9, 84 patients had a DWI-ASPECTS score ≤7. Mean DWI lesion volume was 22.1 (±35) ml. In contrast, by use of >0, >1-, >10-, and >20%-thresholds, median DWI-ASPECTS was 1, 5, 8, and 10; 97.1% (306), 72.7% (229), 41% (129), and 25.7% (81) had DWI-ASPECTS ≤7, respectively. Overall agreement between automated assessment and visual rating was low for every threshold used (>0%: κw = 0.020 1%: κw = 0.151; 10%: κw = 0.386; 20% κw = 0.381). Agreement for dichotomized DWI-ASPECTS ranged from fair to substantial (≤7: >10% κ = 0.48; >20% κ = 0.45; ≤5: >10% κ = 0.528; and >20% κ = 0.695). Conclusion: Overall agreement between automated and the standard used visual scoring is low regardless of the lesion load threshold used. However, dichotomized scoring achieved more comparable results. Varying lesion load thresholds had a critical impact on patient selection by ASPECTS. Of note, the relatively low lesion volume and lack of patients with large artery occlusion in our cohort may limit generalizability of these findings.
EVALuna2:213465

Impaired renal function in stroke patients with atrial fibrillation - Sauer, Eva-Maria; Sauer, Rolf; Kallmuenzer, Bernd; Blinzler, Christian; Breuer, Lorenz; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2014)
Stroke patients with atrial fibrillation (AF) are prone to have comorbidities such as impaired renal function. Because poly-pharmacotherapy is often required in those patients, renal function is important to consider in light of renally cleared medications such as direct oral anticoagulants. In this study, we analyzed frequency and predictors for impaired renal function and its impact on functional outcome in stroke patients with underlying AF.We analyzed 272 patients with acute ischemic stroke and AF of our prospective, observational stroke database. Estimated glomerular filtration rate (eGFR) was calculated on admission and during hospitalization from the equation of the Modification Diet for Renal Disease. Outcome measures included mortality and functional outcome at 90 days, assessed as modified Rankin Scale (mRS) score.On admission, impaired renal function was found in 41.5% (n = 113) and was associated with worse 90-day outcome (mRS score <= 2: 26.5% versus 45.9%, P = .001) and a higher mortality rate (23.9% versus 14.5%, P = .043). Multivariate logistic regression identified older age and history of myocardial infarction as independent predictors of renal dysfunction on admission (P < .05). Normalization of eGFR during hospitalization was achieved in 55.8%.In patients with acute ischemic stroke and AF, impaired renal function on admission is frequent and associated with worse outcome. Normalization of eGFR can often be achieved during hospitalization, but in everyday life, fluctuations of renal function because of infection or dehydration have to be considered. Careful monitoring of renal status is indispensable and should influence drug treatment decisions.
EVALuna2:22248

Increased intima-media thickness in rayon workers after long-term exposure to carbon disulfide - Schramm, Axel; Uter, Wolfgang; Brandt, Meike; Göen, Thomas; Köhrmann, Martin; Baumeister, Thomas; Drexler, Hans (International Archives of Occupational and Environmental Health, 2016)
Long-term exposure to carbon disulfide (CS2) is associated with increased cardiovascular mortality. However, previous studies on actual vascular changes showed heterogeneous results. Intima-media thickness of the carotid arteries (IMT) represents an established marker of atherosclerosis and a reasonable surrogate marker for cardiovascular risk. IMT was examined in a large cohort of CS2 exposed workers and the association with cumulative CS2 exposure analysed.In a cross-sectional examination, 290 exposed and 137 non-exposed workers in a German rayon-manufacturing plant were assessed. Individual cumulative exposure was calculated from this assessment combined with the results of two cross-sectional studies in 1992 and 1999 and department-specific annual means of ambient (CECS2) and individual biological (CETTCA) monitoring results obtained 1992-2009. Furthermore, cumulative duration of working in CS2-exposed departments (CEYEARS) was calculated. Examination included assessment of a broad set of known cardiovascular risk factors and IMT measurement of the carotid arteries on both sides. Multiple linear regression analyses were performed with IMT as outcome and three variants of cumulative exposure (duration of exposure, cumulative CS2, and cumulative TTCA) as well as categorised maximum CS2 exposure, all adjusted for cardiovascular risk factors.All models of cumulative exposure showed a significant increase in IMT in the group with the highest level of exposure: CEYEARS > 20 years, ? = 0.045 mm; CECS2 > 270 ppm × years, ? = 0.052 mm; CETTCA > 33 mg/g creatinine × years, ? = 0.038 mm. Alternatively, addressing maximum exposure, workers with CS2 exposure of >10 ppm in at least 3 years exhibited a significant IMT increase (? = 0.068 mm).Long-term CS2 exposure is an independent risk factor concerning IMT changes. The amount of IMT increase, in a similar range as that associated with other cardiovascular risk factors, might be clinically relevant.
EVALuna2:5493

Increased prevalence of posttraumatic stress disorder in patients after transient ischemic attack - Kiphuth, Ines C.; Utz, Kathrin S.; Noble, Adam J.; Köhrmann, Martin; Schenk, Thomas (Stroke, 2014)
A transient ischemic attack (TIA) involves temporary neurological symptoms but leaves a patient symptom-free. Patients are faced with an increased risk for future stroke, and the manifestation of the TIA itself might be experienced as traumatizing. We aimed to investigate the prevalence of posttraumatic stress disorder (PTSD) after TIA and its relation to patients' psychosocial outcome.Patients with TIA were prospectively studied, and 3 months after the diagnosis, PTSD, anxiety, depression, quality of life, coping strategies, and medical knowledge were assessed via self-rating instruments.Of 211 patients with TIA, data of 108 patients were complete and only those are reported. Thirty-two (29.6%) patients were classified as having PTSD. This rate is 10× as high as in the general German population. Patients with TIA with PTSD were more likely to show signs of anxiety and depression. PTSD was associated with the use of maladaptive coping strategies, subjectively rated high stroke risk, as well as with younger age. Finally, PTSD and anxiety were associated with decreased mental quality of life.The experience of TIA increases the risk for PTSD and associated anxiety, depression, and reduced mental quality of life. Because a maladaptive coping style and a subjectively overestimated stroke risk seem to play a crucial role in this adverse progression, the training of adaptive coping strategies and cautious briefing about the realistic stroke risk associated with TIA might be a promising approach. Despite the great loss of patients to follow-up, the results indicate that PTSD after TIA requires increased attention.
EVALuna2:22311

Invasive stroke treatment - Study results and clinical routine : Lost in translation? - Breuer, L.; Schwab, Sibylle; Köhrmann, Martin (Der Nervenarzt, 2016)
How can the overwhelmingly positive results of the five randomized thrombectomy trials published in 2015 be transferred to the clinical routine?Analysis of trial-specific characteristics with regard to implementation of mechanical thrombectomy into clinical routine.Stroke patients with symptomatic proximal artery occlusion are principally eligible for mechanical thrombectomy; however, the stroke patients included in the thrombectomy trials are not representative of all stroke patients. They were carefully selected according to clinical and imaging criteria as well as to the time window from symptom onset. Furthermore, they were treated in highly selected specialized stroke centers. Analysis of the five trials and the Catalan population-based SONIIA registry revealed that the observed number needed to treat (NNT) of 5 to reach a modified Rankin scale (mRS) score of 0-2 only applies to approximately 1 % of all stroke patients. The NNT for the remaining patients who are principally eligible for thrombectomy requires further study. Currently, centralization seems to be useful to facilitate mechanical thrombectomy in routine care leading to several problems that have to be dealt with in particular regions. Secondary transport to thrombectomy centers plays a major role in this context and has to be provided with highest priority.Only careful analysis of study results and the background circumstances will enable adequate organization and successful practical implementation of this highly effective therapy in the clinical routine. Regional conditions have to be considered and will be crucial in this context.
EVALuna2:22469

Ischemic stroke associated with the use of a synthetic cannabinoid (spice) - Möller, Sebastian; Luecke, Caroline; Struffert, Tobias; Schwarze, Bernhard; Gerner, Stefan; Schwab, Stefan; Köhrmann, Martin; Machold, Kristin; Philipsen, Alexandra; Mueller, Helge H. (Asian Journal of Psychiatry, 2017)
Synthetic cannabinoids, i.e. "spice", are psychoactive drugs with increasing use worldwide. Spice may have harmful neuropsychiatric and physical side effects. Here, we present the case of a 25-year-old man with ischemic stroke after smoking spice on the previous evening. Diagnostic work-up was negative for other common causes of stroke. Toxicology screen unveiled the cannabimimetic ADB-FUBINACA in the drug sample and in patient's urine. The cardiac sympathomimetic effect of spice might have triggered an unnoticed episode of tachyarrhythmia and resulted in stroke via cardioembolic etiology. Thus, in absence of other risk factors, a careful patient history of spice use is recommended for patients with acute neurological deficits.
EVALuna2:22545

Lesion mapping of stroke-related erectile dysfunction - Winder, Klemens; Seifert, Frank; Köhrmann, Martin; Crodel, Carl; Kloska, Stephan; Dörfler, Arnd; Hoesl, Katharina M.; Schwab, Stefan; Hilz, Max-Josef (Brain, 2017)
Acute ischaemic stroke in brain areas contributing to male sexual function may impair erectile function depending on the lesion site. This study intended to determine associations between stroke-related erectile dysfunction and cerebral ischaemic lesion sites using voxel-based lesion mapping. In 52 males (mean age 60.5 ± 10.5 years) with first-ever ischaemic strokes, we assessed erectile function after and retrospectively 3 months prior to the stroke using scores of the 5-item International Index of Erectile Function-5 questionnaire. We assessed cardiovascular risk factors and determined clinical stroke severity and infarct volumes as well as total brain volume by neuroimaging. We calculated correlations between patient age, clinical stroke severity, infarct volumes as well as brain volumes and the difference between erectile dysfunction scores before and after stroke. Moreover, we compared patient age, prevalence of cardiovascular risk factors, clinical stroke severity, infarct volumes and brain volumes of patients with unchanged and deteriorated erectile function after stroke. The infarcts were manually outlined and transformed into stereotaxic space. We determined the lesion overlap and performed subtraction analyses of lesions. In a voxel-based lesion analysis, the difference between erectile dysfunction scores before and after stroke was correlated with the lesion site using t-test statistics. Finally, we conducted a region of interest-based multivariate linear regression analysis that was adjusted for potential confounding factors including patient age, clinical stroke severity, imaging modality, lesion size and brain volume. In 32 patients (61.5%) erectile dysfunction scores declined after the stroke and therefore had stroke-related erectile dysfunction. Deterioration of erectile dysfunction scores was not associated with patient age, clinical stroke severity, infarct volume, brain volume, and cardiovascular risk factors. The voxel-wise subtraction analysis showed associations between stroke-related erectile dysfunction and lesion sites in the right occipito-parietal cortex and thalamus, as well as in the left insula and adjacent temporo-parietal areas. Using voxel-wise t-test statistics, we showed associations between deterioration of erectile function and lesion sites in the right occipital and thalamic region, and the left parietal association area. The linear regression analysis showed that stroke-related erectile dysfunction remained associated with lesions of the right occipital and left parietal association areas after adjusting for confounding factors. In conclusion, our voxel-wise analysis indicates that deteriorating erectile function after stroke is associated with lesions in the right occipito-parietal and thalamic areas integrating visual and somatosensory information, as well as lesions in the left insular and adjacent parieto-temporal areas contributing to generating and mapping visceral arousal states.
EVALuna2:22497

Limited versus Whole-Brain Perfusion for the Indication of Thrombolysis in the Extended Time Window of Acute Cerebral Ischemia - Breuer, Lorenz; Knott, Michael; Struffert, Tobias; Kloska, Stephan; Kurka, Natalia; Schwab, Stefan; Dörfler, Arnd; Köhrmann, Martin; Engelhorn, Tobias (Journal of Stroke and Cerebrovascular Diseases, 2015)
Perfusion computed tomography (PCT) has emerged as alternative to magnetic resonance imaging (MRI) for assessment of patients clinically qualifying for off-label thrombolysis within 4.5 to 9 hours after onset of ischemic stroke. However, disadvantage of PCT is its often limited anatomic coverage with only 2 or 3 slices when using a 4- to 64-section scanner. Our purpose was therefore to evaluate the value of 2- and 3-slice perfusion compared to whole-brain perfusion.One hundred twenty-five patients undergoing MRI beyond 4.5 hours after symptom onset with supratentorial perfusion deficit were selected retrospectively. Accordingly to PCT slice positioning, 2 or 3 slices of the whole-brain perfusion weighted imaging data set were depicted. Volumes of infarct (using cerebral blood volume) and penumbra (using time-to-peak and cerebral blood volume) were calculated, and results were compared with 2- and 3-slice-derived volumes, respectively.Whole-brain imaging revealed a mismatch of more than 20% in 68.8% of patients (defined as 100%). Two-slice imaging detected a perfusion deficit in 72% and a mismatch in 48.8% (sensitivity = 70.9%). Three-slice imaging detected a perfusion deficit in 76% and a mismatch in 50.4% (sensitivity = 73.3%). Although there was no significant difference between 2- and 3-slice imaging (P > .23), both techniques revealed significantly less patients with mismatch compared to whole-brain coverage (P < .01).Two- and 3-slice imaging like obtained with PCT on most installed CT systems to assess perfusion deficits with subsequent mismatch calculation in acute stroke outside the 4.5-hour time window is significantly inferior to whole-brain coverage and, hence, has to be considered as a less-than-ideal solution.
EVALuna2:22358

Logistical and financial obstacles for endovascular therapy of acute stroke implementation - Schellinger, Peter D.; Köhrmann, Martin; Nogueira, Raul G. (International Journal of Stroke, 2016)
After publication of the recent positive randomized clinical endovascular trials, several questions and obstacles for wide spread implementation remain. We address specific issues namely efficacy, safety, logistics, timing, sedation, numbers, imaging, manpower, centers, geographics, and economical aspects of endovascular therapy. As we move forward, a high degree of collaboration will be crucial to implement a therapy with established overwhelming treatment efficacy for severe acute stroke patients.
EVALuna2:22456

Neuroanatomical correlates of severe cardiac arrhythmias in acute ischemic stroke - Seifert, Frank; Kallmünzer, Bernd; Gutjahr, Isabell; Breuer, Lorenz; Winder, Klemens; Kaschka, Iris; Kloska, Stephan; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin (Journal of Neurology, 2015)
Neurocardiological interactions can cause severe cardiac arrhythmias in patients with acute ischemic stroke. The relationship between the lesion location in the brain and the occurrence of cardiac arrhythmias is still discussed controversially. The aim of the present study was to correlate the lesion location with the occurrence of cardiac arrhythmias in patients with acute ischemic stroke. Cardiac arrhythmias were systematically assessed in patients with acute ischemic stroke during the first 72 h after admission to a monitored stroke unit. Voxel-based lesion-symptom mapping (VLSM) was used to correlate the lesion location with the occurrence of clinically relevant severe arrhythmias. Overall 150 patients, 56 with right-hemispheric and 94 patients with a left-hemispheric lesion, were eligible to be included in the VLSM study. Severe cardiac arrhythmias were present in 49 of these 150 patients (32.7%). We found a significant association (FDR correction, q < 0.05) between lesions in the right insular, right frontal and right parietal cortex as well as the right amygdala, basal ganglia and thalamus and the occurrence of cardiac arrhythmias. Because left- and right-hemispheric lesions were analyzed separately, the significant findings rely on the 56 patients with right-hemispheric lesions. The data indicate that these areas are involved in central autonomic processing and that right-hemispheric lesions located to these areas are associated with an elevated risk for severe cardiac arrhythmias.
EVALuna2:22355

Neuroanatomic correlates of poststroke hyperglycemia - Winder, Klemens; Seifert, Frank; Ohnemus, Tessa; Sauer, Eva-Maria; Kloska, Stephan; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin (Annals of Neurology, 2015)
A study was undertaken to determine associations between ischemic stroke sites and poststroke hyperglycemia (PSH).Nondiabetic patients with first ever ischemic stroke confirmed by imaging were prospectively included. Blood glucose level (BGL), National Institute of Health Stroke Scale (NIHSS) score, and clinical parameters were assessed on admission. BGL was dichotomized for elevated versus normal levels using a cutoff value of >7.0 mmol/l. Clinical parameters were correlated with BGL and were compared between patient groups with elevated versus normal glucose values. A voxel-based lesion symptom mapping (VLSM) analysis adjusted for confounding variables was performed correlating sites of ischemic lesions with PSH.Of 1,281 stroke patients screened, 229 (mean age = 66.3 ± 15.9 years) met the inclusion criteria. Patients with elevated BGL were older, had higher NIHSS scores, and had larger infarcts compared to those without elevated glucose levels. Spearman rank analysis showed correlations between BGL and age, infarct size, heart rate (HR), and NIHSS scores (p <= 0.05). The VLSM analysis adjusted for these confounding factors demonstrated associations between PSH and damaged voxels in right hemispheric insular and opercular areas.The data indicate that damage in the right insulo-opercular areas contributes to PSH. The association between sympathetically mediated increase of HR and BGL suggests disinhibition of sympathetic outflow as a possible mechanism for PSH.
EVALuna2:22352

Neuroendocrine changes in patients with spontaneous supratentorial intracerebral hemorrhage - Huttner, Hagen; Kiphuth, Ines-Christine; Teuber, Linda; Lücking, Hannes; Kloska, Stephan; Staykov, Dimitre; Kuramatsu, Joji; Mauer, Christoph; Breuer, Lorenz; Dörfler, Arnd; Köhrmann, Martin (Neurocritical Care, 2013)
Background: Neuroendocrine changes have been reported after ischemic stroke, subarachnoid hemorrhage, and brain trauma. As there are no corresponding data in patients with intracerebral hemorrhage (ICH) we analyzed various neuroendocrine parameters to investigate possible alterations in hormone profiles of patients with ICH. Methods: Twenty patients with ICH were prospectively enrolled in the study. Patients were a priori parted into two groups: Ten non-ventilated patients treated on the stroke-unit (hemorrhage volumes <20 ml, "small ICH"), and 10 ventilated patients treated on the neurocritical care unit (hematoma volumes >20 ml with possible additional ventricular involvement ("large ICH"). Neuroendocrine parameters were compared between both groups referring to reference values. The following parameters were obtained over a period of 9 days in 20 patients with spontaneous supratentorial ICH: thyrotropin, free thiiodothyronine and thyroxine, human growth hormone, insulin-like growth factor 1, luteinizing hormone, follicle-stimulating hormone, testosterone, prolactin, adrenocorticotropic hormone, and cortisol. Results: Small ICH patients were in a median 71 (54-88) years old and had a mean ICH volume of 9.5 ± 6.5 ml, whereas large ICH patients were 65 (47-80) years old and showed a mean volume of 56 ± 30.2 ml. None of the patients revealed pathological alterations for thyrotropin, free thiiodothyronine, thyroxine, human growth hormone, insulin-like growth factor 1, and testosterone. There was only a mild decrease of adrenocorticotropic hormone and cortisol on day 3 in large ICH patients. Small ICH patients showed pathologically elevated levels of luteinizing and follicle-stimulating hormone throughout the observation period. Large ICH patients showed a marked increase of prolactin that developed during the course. Conclusions: Overall, neuroendocrine changes in ICH patients are not as profound as reported for ischemic stroke or subarachnoid hemorrhage. The clinical significance of increased LH and FSH levels in small ICH is unclear, whereas elevation of prolactin in large ICH was anticipated. Future randomized controlled trials should also focus on neuroendocrine parameters to clarify the impact of possible hormonal alterations on functional outcome. © 2011 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hormone profile; Intracerebral hemorrhage; Neuroendocrine

Partial pharmacologic blockade shows sympathetic connection between blood pressure and cerebral blood flow velocity fluctuations - Hilz, Max-Josef; Wang, Ruihao; Marthol, Harald; Liu, Mao; Tillmann, Alexandra; Riss, Stephan; Hauck, Paulina; Hoesl, Katharina M.; Wasmeier, Gerald; Stemper, Brigitte; Köhrmann, Martin (Journal of the Neurological Sciences, 2016)
Cerebral autoregulation (CA) dampens transfer of blood pressure (BP)-fluctuations onto cerebral blood flow velocity (CBFV). Thus, CBFV-oscillations precede BP-oscillations. The phase angle (PA) between sympathetically mediated low-frequency (LF: 0.03-0.15Hz) BP- and CBFV-oscillations is a measure of CA quality. To evaluate whether PA depends on sympathetic modulation, we assessed PA-changes upon sympathetic stimulation with and without pharmacologic sympathetic blockade. In 10 healthy, young men, we monitored mean BP and CBFV before and during 120-second cold pressor stimulation (CPS) of one foot (0°C ice-water). We calculated mean values, standard deviations and sympathetic LF-powers of all signals, and PAs between LF-BP- and LF-CBFV-oscillations. We repeated measurements after ingestion of the adrenoceptor-blocker carvedilol (25mg). We compared parameters before and during CPS, without and after carvedilol (analysis of variance, post-hoc t-tests, significance: p<0.05). Without carvedilol, CPS increased BP, CBFV, BP-LF- and CBFV-LF-powers, and shortened PA. Carvedilol decreased resting BP, CBFV, BP-LF- and CBFV-LF-powers, while PAs remained unchanged. During CPS, BPs, CBFVs, BP-LF- and CBFV-LF-powers were lower, while PAs were longer with than without carvedilol. With carvedilol, CPS no longer shortened resting PA. Sympathetic activation shortens PA. Partial adrenoceptor blockade abolishes this PA-shortening. Thus, PA-measurements provide a subtle marker of sympathetic influences on CA and might refine CA evaluation.
EVALuna2:22459

Peripheral pulse measurement after ischemic stroke: A feasibility study - Kallmünzer, Bernd; Bobinger, Tobias; Kahl, Nicolas; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Marquardt, Lars; Schwab, Stefan; Köhrmann, Martin (Neurology, 2014)
To investigate feasibility and diagnostic accuracy of measurement of the peripheral pulse (MPP) at the radial artery as a simple, noninvasive screening tool for paroxysmal atrial fibrillation (pAF) in patients after acute ischemic stroke.Two hundred fifty-six patients with acute ischemic stroke and the patients' relatives at a tertiary stroke center were prospectively included. Participants were instructed for characteristics of atrial fibrillation (AF) in MPP using standardized educational material. Measurements of participants as well as a health care professional were then compared with simultaneous blinded ECG to evaluate diagnostic accuracy parameters.MPP by the health care professional or patients' relatives had a diagnostic sensitivity of 96.5% and 76.5%, respectively, with 94.0% and 92.9% specificity for the detection of AF. Self-measurements were reliably performed by 89.1% of competent patients with a diagnostic sensitivity of 54.1% and 96.2% specificity. False-positive results were limited to 6 cases (2.7%) with a positive predictive value of 76.9% and a negative predictive value of 90.0%.With a low rate of false-positive results, MPP offers an easy, ubiquitously available, noninvasive, first-step screening tool to guide ECG diagnostics for pAF after ischemic stroke. The data warrant a prospective trial evaluating the efficacy of MPP-guided ECG diagnostics in secondary prevention after stroke, which is now underway.This study provides Class I evidence that MPP by patients or relatives accurately distinguishes AF from normal heart rhythm as compared with continuous ECG.
EVALuna2:22299

Prevalence and impact on outcome of electrocardiographic early repolarization patterns among stroke patients: a prospective observational study - Bobinger, Tobias; Kallmünzer, Bernd; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Clinical Research in Cardiology, 2015)
Early repolarization pattern (ER) gained attention as a risk factor for ventricular arrhythmia and sudden cardiac death in the general population. While electrocardiographic abnormalities are frequent findings in stroke patients, data on ER pattern in this population are lacking.We assessed the prevalence of ER pattern in consecutive acute stroke patients at a tertiary stroke center. Functional outcome after 90 days was analyzed to determine the effect of an ER pattern on mortality. Multivariate logistic regression analysis was used to identify factors associated with an ER pattern.Out of 1141 consecutive stroke patients 771 patients remained for analysis after application of exclusion criteria. ER was observed in 62 (8.04%) patients. ER was more prevalent among subjects with intracerebral and subarachnoidal hemorrhage (13.0%) than among patients with ischemic stroke (7.0%; p = 0.024). Multiple regression analysis revealed QRS-duration (OR 0.972 95% CI 0.950-0.994, p = 0.012), QT-duration (OR 1.009, 95% CI 1.004-1.014, p = 0.001) and mechanical ventilation on admission (OR 0.320, 95% CI 0.136-0.752, p = 0.009) as independent predictors for ER. Overall ER on admission was not associated with increased mortality at 3-month follow-up (ER 11.3% vs. non-ER 9.2%; p = 0.582).ER is frequently found among patients with acute cerebrovascular events and is more prevalent in patients with hemorrhagic compared to ischemic events. Our study yields no evidence that ER is associated with worse outcome or mortality after stroke.
EVALuna2:12024

Reliability and limitations of automated arrhythmia detection in telemetric monitoring after stroke - Kurka, Natalia; Bobinger, Tobias; Kallmünzer, Bernd; Koehn, Julia; Schellinger, Peter D.; Schwab, Stefan; Köhrmann, Martin (Stroke, 2015)
Guidelines recommend continuous ECG monitoring in patients with cerebrovascular events. Studies on intensive care units (ICU) demonstrated high sensitivity but high rates of false alarms of monitoring systems resulting in desensitization of medical personnel potentially endangering patient safety. Data on patients with acute stroke are lacking.One-hundred fifty-one consecutive patients with acute cerebrovascular events were prospectively included. Automatically identified arrhythmia events were analyzed by manual ECG analysis. Muting of alarms was registered. Sensitivity was evaluated by beat-to-beat analysis of the entire recorded ECG data in a subset of patients. Ethics approval was obtained by University of Erlangen-Nuremberg.A total of 4809.5 hours of ECG registration and 22 509 alarms were analyzed. The automated detection algorithm missed no events but the overall rate of false alarms was 27.4%. Only 0.6% of all alarms indicated acute life-threatening events and 91.4% of these alarms were incorrect. Transient muting of acoustic alarms was observed in 20.5% patients.Continuous ECG monitoring using automated arrhythmia detection is highly sensitive in acute stroke. However, high rates of false alarms and alarms without direct therapeutic consequence cause desensitization of personnel. Therefore, acoustic alarms may be limited to life-threatening events but standardized manual evaluation of all alarms should complement automated systems to identify clinically relevant arrhythmias.
EVALuna2:22266

Safety and efficacy of sonothrombolysis for acute ischaemic stroke: a multicentre, double-blind, phase 3, randomised controlled trial - Alexandrov, Andrei; Köhrmann, Martin; Soinne, Lauri; Tsivgoulis, Georgios; Barreto, Andrew D.; Demchuk, Andrew M.; Sharma, Vijay K.; Mikulik, Robert; Muir, Keith W.; Brandt, Gordon; Alleman, John; Grotta, James C.; et al. (Lancet Neurology, 2019)
Background Pulsed-wave ultrasound increases the exposure of an intracranial thrombus to alteplase (recombinant tissue plasminogen activator), potentially facilitating early reperfusion. We aimed to ascertain if a novel operator-independent transcranial ultrasound device delivering low-power high-frequency ultrasound could improve functional outcome in patients treated with alteplase after acute ischaemic stroke.
CRIS-Team WoS Importer:2019-03-26

Seizures among long-term survivors of conservatively treated ICH patients: incidence, risk factors, and impact on functional outcome - Madzar, Dominik; Kuramatsu, Joji; Gollwitzer, Stephanie; Lücking, Hannes; Kloska, Stephan; Hamer, Hajo; Köhrmann, Martin; Huttner, Hagen (Neurocritical Care, 2014)
Seizures are a common complication after intracerebral hemorrhage (ICH) but there is a substantial lack of information on the long-term incidence in ICH survivors and whether post-ICH seizures affect functional long-term outcome.Over a five-year period 464 consecutive patients with spontaneous ICH were analyzed. Focussing on 1-year ICH survivors, clinical, and radiological parameters were retrieved from institutional prospective databases. The occurrence of seizures was categorized as early (<=7 days) or late (>7 days). Functional outcome was assessed by mailed questionnaires and telephone interviews, and was categorized into good vs. poor (mRS: 0-2 vs. 3-5) and favorable vs. unfavorable (mRS: 0-3 vs. 4-5). Multivariate regression models were calculated to investigate risk factors associated with post-ICH seizures including an a priori defined subgroup analysis of lobar ICH patients.Among 203 long-term ICH survivors, 19.7 % developed seizures of which 55 % occurred late. Factors associated with seizures were lobar location (OR 8.10; 95 % CI 3.04-21.59; p < 0.001), sepsis (OR 4.59; 95 % CI 1.20-17.53; p = 0.026), and history of alcohol abuse (OR 3.36; 95 % CI 1.25-9.06; p = 0.017). Subgroup analysis of lobar ICH patients revealed history of alcohol abuse as the only independent predictor of post-ICH seizures (OR 5.22; 95 % CI 1.25-21.78; p = 0.024). Functional long-term outcome among survivors was slightly worse in patients with post-ICH seizures (p = 0.059). In multivariate regression modeling for prediction of poor outcome, the parameter "post-ICH seizures" again reached a statistical trend (p = 0.065), and established parameters such as age, GCS, and hemorrhage volume were independently related to poor outcome.Post-ICH seizures among long-term ICH survivors are common and may contribute to unfavorable functional outcome. Especially lobar ICH patients with a history of alcohol abuse are at risk to develop post-ICH seizures. Therefore, this subgroup may represent a target population for a prophylactic anticonvulsive treatment approach, preferably investigated in a prospective randomized trial.
EVALuna2:22307

Teaching NeuroImages: Stroke and bilateral visual loss in a young adult: More than coincidence - Volbers, Bastian; Kaldefoss, K.; Bergua, A.; Kloska, Stephan; Schwab, Sibylle; Köhrmann, Martin (Neurology, 2012)
EVALuna2:21072

The hyperintense acute reperfusion marker on fluid-attenuated inversion recovery magnetic resonance imaging is caused by gadolinium in the cerebrospinal fluid - Köhrmann, Martin; Struffert, Tobias; Frenzel, Thomas; Schwab, Stefan; Dörfler, Arnd (Stroke, 2012)
Background and PurposeS-: The hyperintense acute reperfusion marker (HARM) on fluid-attenuated inversion recovery MRI is believed to be caused by gadolinium-based contrast agents crossing a disrupted blood-brain barrier. However, this hypothesis has never been directly verified in humans. Methods-: In this study, we analyzed cerebrospinal fluid samples of patients with HARM on imaging regarding the presence and concentration of gadolinium-based contrast agents. Results-: Gadobutrol was found in concentrations of approximately 50 μmol/L. Using phantom MRI experiments, we demonstrate that the detected concentrations are consistent with the observed HARM imaging pattern. Conclusions-: Our study yields first direct evidence in humans that the imaging phenomenon HARM is indeed caused by leakage of gadolinium-based contrast agents into the cerebrospinal fluid. © 2011 American Heart Association. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: FLAIR; hyperintensive acute reperfusion marker; MRI

Validity of acute stroke lesion volume estimation by diffusion-weighted imaging-Alberta Stroke Program Early Computed Tomographic Score depends on lesion location in 496 patients with middle cerebral artery stroke - Schroeder, Julian; Cheng, Bastian; Ebinger, Martin; Köhrmann, Martin; Wu, Ona; Kang, Dong-Wha; Liebeskind, David S.; Tourdias, Thomas; Singer, Oliver C.; Christensen, Soren; Campbell, Bruce; Luby, Marie; et al. (Stroke, 2014)
Alberta Stroke Program Early Computed Tomographic Score (ASPECTS) has been used to estimate diffusion-weighted imaging (DWI) lesion volume in acute stroke. We aimed to assess correlations of DWI-ASPECTS with lesion volume in different middle cerebral artery (MCA) subregions and reproduce existing ASPECTS thresholds of a malignant profile defined by lesion volume >=100 mL.We analyzed data of patients with MCA stroke from a prospective observational study of DWI and fluid-attenuated inversion recovery in acute stroke. DWI-ASPECTS and lesion volume were calculated. The population was divided into subgroups based on lesion localization (superficial MCA territory, deep MCA territory, or both). Correlation of ASPECTS and infarct volume was calculated, and receiver-operating characteristics curve analysis was performed to identify the optimal ASPECTS threshold for >=100-mL lesion volume.A total of 496 patients were included. There was a significant negative correlation between ASPECTS and DWI lesion volume (r=-0.78; P<0.0001). With regards to lesion localization, correlation was weaker in deep MCA region (r=-0.19; P=0.038) when compared with superficial (r=-0.72; P<0.001) or combined superficial and deep MCA lesions (r=-0.72; P<0.001). Receiver-operating characteristics analysis revealed ASPECTS<=6 as best cutoff to identify >=100-mL DWI lesion volume; however, positive predictive value was low (0.35).ASPECTS has limitations when lesion location is not considered. Identification of patients with malignant profile by DWI-ASPECTS may be unreliable. ASPECTS may be a useful tool for the evaluation of noncontrast computed tomography. However, if MRI is used, ASPECTS seems dispensable because lesion volume can easily be quantified on DWI maps.
EVALuna2:22292

Vasospasm in intracerebral hemorrhage with ventricular involvement: a prospective pilot transcranial Doppler sonography study - Kiphuth, Ines C.; Huttner, Hagen; Breuer, Lorenz; Engelhorn, Tobias; Schwab, Stefan; Köhrmann, Martin (Cerebrovascular Diseases, 2011)
Cerebral vasospasm (VSP) is a common complication after subarachnoid hemorrhage (SAH), but has rarely been reported after intracerebral hemorrhage (ICH) without subarachnoidal bleeding. The underlying pathophysiological mechanism is mainly mediated by circulating heme products within the cerebrospinal fluid, and thus patients with ICH and ventricular involvement (IVH) may also be in danger of developing VSP. The incidence and role of VSP in IVH, however, have not been systematically studied.We prospectively enrolled 115 patients with ICH with or without IVH into the study between April 2009 and April 2010. All patients received serial extracranial and transcranial Doppler sonography (TCD) at baseline, on days 3-5 and 7-9 to detect and monitor VSP. In addition, CT scans taken on admission, after 24 h and before discharge were evaluated for the occurrence of delayed cerebral ischemia.Three out of 53 patients (5.7%) with IVH showed a significant elevation of flow velocities over the examined timeframe. One of these patients developed severe VSP resulting in secondary ischemic infarction. None of the ICH patients without IVH showed significantly elevated flow velocities or secondary infarction.Cerebral VSP with secondary infarction may occur in patients with spontaneous IVH, though far less frequently than in SAH; thus, systematic screening of all patients with IVH may not be warranted. However, serial TCD should be considered in patients with secondary clinical worsening or extensive IVH.
EVALuna2:21961

Vorhofohrverschluss bei Vorhofflimmern? Kontra - Schellinger, P. D.; Köhrmann, Martin (Der Nervenarzt, 2015)
EVALuna2:22380